PENGARUH PENEMPATAN KERJA TERHADAP KINERJA KARYAWAN PKP-PK PADA PT.ANGKASA PURA II (PESERO) CABANG BANDARA SULTAN MAHMUD BADARUDDIN II PALEMBANG - Muhammad Ridwan; Galih Ujiantoro (Fakultas Ekonomi Universitas Tridinanti Palembang, 2015)
Goal we want to achieve in this study was to determine the effect of Recruitment and Selection Process for Employee Performance PKP-PK at PT. Angkasa Pura II (Persero) Branch Sultan Mahmud Badaruddin II Palembang. With the sample used in this study, 38 employees. Data was collected through a questionnaire to all employees sharing PKP- PK At PT. Angkasa Pura II (Persero) Branch Sultan Mahmud Badaruddin II Palembang.Recruitment Process (X1) and Selection (X2) simultaneously affect the performance (Y) obtained the value of F at (107.815)> F table (3.25) and sig 0.000 <0.05 then H0 is rejected and H1 is accepted, meaning Recruitment Process and Selection simultaneously affect significantly (significantly) on employee performance PKP-PK at PT. Angkasa Pura II, the airport branch of Sultan Mahmud Badaruddin II Palembang.The recruitment process (X1) effect on performance (Y) obtained tcount of 4.750> t table (2,021) and sig 0.000 <0.05 then H0 is rejected and H1 is accepted, meaning Recruitment Process partially affect significantly (significantly) on employee performance PKP -PK at PT. Angkasa Pura II, the airport branch of Sultan Mahmud Badaruddin II Palembang.Selection (X2) partially affect the performance (Y) obtained tcount of 4.491> t table (2,021) and sig 0.000 <0.05 then H0 is rejected and H1 is accepted, meaning Selection partially affect significantly (significantly) on employee performance PKP -PK at PT. Angkasa Pura II, the airport branch of Sultan Mahmud Badaruddin II Palembang.The performance (Y) is influenced by the Recruitment Process (X1) and Selection (X2). The coefficient of determination (R2) between the recruitment process (X1) and selection (X2) on the performance (Y). obtained value of Adjusted R Square = 0.852 means that 85.2% of the performance variable (Y) is affected by the recruitment process (X1) and selection (X2). And the rest of it by 14.8% influenced by other variables.Keywords: Influence, Recruitment, Selection, Performance.